Severe thiamine deficiency in sheep with acute ruminal lactic acidosis - Karapinar, T.; Dabak, M.; Kizil, O.; Balikci, E. (Blackwell Publishing, 2008)
Background: Thiamine status of ruminants is adversely affected in acidic rumen conditions. However, there have been limited published case study data related to thiamine deficiency of ruminants with acute ruminal lactic acidosis (ARLA). Hypothesis: Thiamine deficiency would occur in sheep with ARLA. Animals: Thirteen Ak-Karaman (white Karaman) sheep with ARLA, aged 1 year (ARLA group) and 10 healthy Ak-Karaman sheep, aged 1 year (control group) were used. Methods: After clinical examination, rumen fluid samples of all sheep were obtained with a stomach tube and examined immediately. Blood samples were taken from a jugular vein of the sheep. Erythrocytic transketolase enzyme activity and hence thiamine pyrophosphate (TPP) effect were determined according to Clausen's method. Results: History revealed that all sheep in the ARLA group had accidentally consumed excessive amounts of cracked barley. During clinical examination of the ARLA group, disturbed general condition, engorged scleral vessels, moderate to severe dehydration, and ruminal atony were recorded in the sheep. The results of the ruminal fluid analyses of the ARLA group demonstrated characteristics of ARLA. The results of clinical and ruminal fluid examination of control group were normal. The mean TPP effect (%) in the ARLA group (109 +/- 28) was significantly higher than in the control group (22.2 +/- 3.7) (P < .001). Conclusions and Clinical Importance: The present study revealed that severe thiamine deficiency occurred in sheep with ARLA. This result indicates that thiamine administration to sheep suffering from acute ruminal acidosis caused by overconsumption of readily fermentable carbohydrates could be beneficial in alleviating thiamine deficiency caused by ruminal acidosis.
Keywords: grain overload; polioencephalomalacia; transketolase test; vitamin B1